PSIV-10 Preference evaluation of plant functional types grasses in calves. (5th December 2019) - Vulliez, María A; Bruni, María; Trujillo, Ana I; Durante, Martín; Lezana, Lucrecia; Soca, Pablo
Abstract: The functional types of plants (PFT) ecological approach could be used to link the preferences of ruminants. In order to investigate if ruminant preferences were associated with this approach, three PFT groups were evaluated. A group "B", represented by Paspalum urvillei (PU-B), "C" by Nassella neesiana (NN-C) and Sporobolus indicus (SI-C) and "D" by Andropogon lateralis (AL-D). In a randomized block design with repeated measures over time, two independent cafeteria trials (autumn-winter, A-W, and spring-summer, S-S) were carried out in calves (n = 8 for A-W; n = 4 for S-S; BW=240–270 kg) arranged in four pens. In three sessions of ten minutes each, calves received 120–160 gDM of fresh cut leaves from the different species. Dry matter intake (DMI), nitrogen intake (NI) and neutral detergent fiber intake (NDFI) were measured. Data were analyzed with a mixed model that included specie and session as fixed effects and blocks as a random. The statistical analyses were performed with SAS (University Edition), data is expressed as lsmeans and was considered to differ when Tukey test presented P < 0.05. No significant differences were observed between sessions. The DMI and NI were higher in NN-C and lower in AL-D (P < 0.01) during A-W. However, in S-S, higher DMI and NI were observed in AL-D and SI-C while NN-C presented the lower DMI and NI (P < 0.01). The FDNI did not show differences in A-W meanwhile in S-S was positively associated with DMI (Table1). Interestingly, when the season changed, it was observed a change in PFT preference, in A-W calves preferred NN-C whereas in S-S preferred AL-D. However, attributes associated with preferences were maintained in both stations, for instance, higher DMI was associated with higher NI. Additional research is required on the interactions between PFT approach and the preference of animals for different species.